DELIVERY PERFORMANCE MEASUREMENT IN AN INTEGRATED SUPPLY CHAIN MANAGEMENT: CASE STUDY IN BATTERIES MANUFACTURING FIRM - V.V. Muniswamy; K. Prahlada Rao; C. Madhusudhana Rao (Serbian Journal of Management, 2011)
Delivery performance provides an indication of how successful the supply chain is at providingproducts and services to the customer. This metric is most important in supply chain management asit integrates the measurement of performance right from supplier end to the customer end. Presentresearch is focused on a case study conducted in a leading batteries manufacturing firm in SouthIndia and analysis of elemental performances in overall delivery performance of an entire supplychain in an integrated approach. NLP and Dynamic Programming models have been used to getoptimal and sub-optimal solutions to help firms in benchmarking expected performance levels. Theeffect of learning has also been described with an empirical analysis.